Leonurus cardiaca L. herb - a derived extract and an ursolic acid as the factors affecting the adhesion capacity of Staphylococcus aureus in the context of infective endocarditis - Micota, Bartłomiej; Sadowska, Beata; Podsędek, Anna; Redzynia, Małgorzata; Różalska, Barbara (Polish Biochemical Society, 2014)
The objective was an assessment of the impact of Leonurus cardiaca L. extract (LCE) and ursolic acid (UA) on the adhesive properties of Staphylococus aureus NCTC 8325 strain, expressing virulence factors important in the pathogenesis of infective endocarditis. The adhesion and biofilm formation of bacteria cultured in the presence of subinhibitory concentrations of LCE or UA on the abiotic surface or covered with fibrinogen, fibronectin or collagen, were evaluated. Inhibitory effects of LCE and UA on staphylococcal adherence to both types of surface were demonstrated. This, in the case of UA, resulted in a significant reduction of biofilm formation.
Keywords: ECM; Leonurus cardiaca; ursolic acid; Staphylococcus aureus